Effects and contributory factors of sulfur-fumigation on the efficacy and safety of medicinal herbs evaluated by meta-analysis. (15th July 2022) - Liu, Hui; Wang, Si-Yu; Zhu, Jin-Hao; Kong, Ming; Zhou, Shan-Shan; Li, Song-Lin; Zhu, He
Abstract: Ethnopharmacological relevance: Sulfur-fumigation undoubtedly alters the chemical and metabolic profiles, but controversially affects the efficacy and safety of medicinal herbs. Aim of the study: To comprehensively evaluate the effects of sulfur-fumigation on the efficacy and safety of medicinal herbs using a meta-analysis approach and further investigate the potential contributory factors. Materials and methods: Literatures were retrieved on PubMed, Web of Science, Embase, China National Knowledge Infrastructure, Chinese VIP Information and Wanfang, and the outcomes involved activities and toxicities were extracted using standard data extraction forms. The effects of sulfur-fumigation on the efficacy and safety of medicinal herbs were evaluated by meta-analysis approaches. Results: A total of sixteen studies were included in this study. Sulfur-fumigation reduced the efficacies of medicinal herbs with immune activity [thymus index (SMD = −1.81; P < 0.00001); spleen index (SMD = −1.11; P < 0.0001)], anti-oxidative activity [MDA (SMD = 2.60; P = 0.04); SOD (SMD = −2.21; P < 0.00001)], analgesic activity [heat tolerate time (SMD = −2.51; P = 0.001); writhing time (SMD = 0.36; P = 0.006)], anti-platelet aggregation activity (SMD = −1.84; P = 0.001), and anti-inflammatory activity [ear swelling degree (SMD = 0.47; P = 0.006)]. The reductions might be ascribed to sulfur-fumigation significantly reduced the contents of active ingredients in medicinal herbs, leading to dramatic decrease in the absorption of these ingredients and their metabolites in vivo . Furthermore, sulfur-fumigation induced the toxicities of medicinal herbs, mainly on hepatotoxicity, which might due to fumigation-induced residues of sulfur dioxide and heavy metal, and generations of sulfur-containing derivatives and toxic metabolites. Besides, administrated with sulfur-fumigated medicinal herbs with high sulfur ratio and/or higher dosage showed more significant toxicity. Conclusion: Sulfur-fumigation reduced the efficacy and safety of medicinal herbs, indicating sulfur-fumigation might not a feasible approach to process medicinal herbs. However, with obvious limitations, much more rigorous designed-trials are still needed to confirm the conclusion. Graphical abstract: Image 1